Production Aspects of Lengger Dance in the Taruna Budaya Art Group Sendangsari Wonosobo Regency - Zulia Sukma; Arsih, Utami; Pramesti Putri, Rimasari (Universitas Negeri Semarang, 2025)
Arts groups that grow from the community have a big role in maintaining and preserving local cultural heritage. Even so, the way they manage performances, especially in the Taruna Budaya Arts Group, is still rarely discussed in depth. This research tries to describe how the production management of Lengger Dance performances is carried out by a group that has existed since 1996 in Sendangsari Village, Garung District, Wonosobo. With two main divisions - dance and karawitan - this group involves cross-generations in its implementation and management. With a descriptive qualitative approach, data were obtained through observation, in-depth interviews, and documentation techniques. The data were then analyzed through the stages of data reduction, information presentation, and conclusion drawing. The study findings show that the group's success in managing performances is supported by the application of the four main principles proposed by George R. Terry: (1) planning such as the preparation of training schedules, open recruitment, and increasing the intensity of training, (2) the organizing stage through delegation of roles in production, (3) the movement stage through coordination involving the dance division and, and (4) the supervision stage with regular collective evaluations. The results show that this art group applies classical management whose process consists of four principles.